1991
DOI: 10.1002/jbt.2570060104
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in de novo pyrimidine biosynthesis during uridine reversal of pyrazofurin‐inhibited dna synthesis

Abstract: Pyrazofurin, a pyrimidine nucleoside analogue with antineoplastic activity, inhibits cell proliferation and DNA synthesis in cells by inhibiting uridine 5'-phosphate (UMP) synthase. It has been previously shown in concanavalin A (con A)-stimulated guinea pig lymphocytes (23) that pyrazofurin-inhibited DNA synthesis could be selectively reversed by exogenous uridine (Urd). In this report, we have examined possible mechanisms for the Urd reversal with experiments that determine the ability of exogenous Urd to (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…To test this hypothesis, we first treated cells with small molecule inhibitors of pyrimidine and purine metabolism, which generate the ribonucleotide precursors that RNR reduces to dNTPs in a GSH-dependent manner. Cells were pretreated with mycophenolic acid (MPA), to inhibit the purine synthetic enzyme inosine-5′-monophosphate dehydrogenase (IMPDH), or with pyrazofurin (Pyr), to inhibit the pyrimidine synthetic enzyme orotidine 5'-monophosphate decarboxylase (UMPS) (Fleming et al, 1996;Ringer et al, 1991). Nucleotide depletion itself triggers p53 stabilization, and we confirmed that both MPA and Pyr caused this effect in HT-1080 Control cells (Figure 4A).…”
Section: Rnr Inhibition Blocks Ferroptosissupporting
confidence: 71%
“…To test this hypothesis, we first treated cells with small molecule inhibitors of pyrimidine and purine metabolism, which generate the ribonucleotide precursors that RNR reduces to dNTPs in a GSH-dependent manner. Cells were pretreated with mycophenolic acid (MPA), to inhibit the purine synthetic enzyme inosine-5′-monophosphate dehydrogenase (IMPDH), or with pyrazofurin (Pyr), to inhibit the pyrimidine synthetic enzyme orotidine 5'-monophosphate decarboxylase (UMPS) (Fleming et al, 1996;Ringer et al, 1991). Nucleotide depletion itself triggers p53 stabilization, and we confirmed that both MPA and Pyr caused this effect in HT-1080 Control cells (Figure 4A).…”
Section: Rnr Inhibition Blocks Ferroptosissupporting
confidence: 71%
“…To test this hypothesis, we first treated cells with small molecule inhibitors of pyrimidine and purine metabolism, which generate the ribonucleotide precursors that RNR reduces to dNTPs in a GSH-dependent manner. Cells were pretreated with mycophenolic acid (MPA), to inhibit the purine synthetic enzyme inosine-59-monophosphate dehydrogenase, or with pyrazofurin (Pyr), to inhibit the pyrimidine synthetic enzyme orotidine 5'-monophosphate decarboxylase (UMPS) (Ringer et al, 1991;Fleming et al, 1996). Nucleotide depletion itself triggers p53 stabilization, and we confirmed that both MPA and Pyr caused this effect in HT-1080 Control cells (Fig 4A).…”
Section: Rnr Inhibition Blocks Ferroptosissupporting
confidence: 58%
“…Pyrazofurin was found to inhibit the orotidine 5′monophosphate decarboxylase activity of UMPS as a nucleoside analogue in the last century with high efficacy especially in acute myelogenous leukemia patients (162). Nevertheless, the resistance to pyrazofurin appeared early in clinical (163)(164)(165).…”
Section: Pyrazofurinmentioning
confidence: 99%